DESIGN AND DEVELOPMENT OF CONTROL MONITORING FOR REAL-TIME CLOCK (RTC) IMPLEMENTATION IN A SOLAR CELL TRACKER USING NAIVE BAYES METHOD BASED ON WEB SERVICE - Nanditta, Meyra; Yunior, Yudhis Thiro Kabul; Sukma, Meita Maharani (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
The efficiency of solar panels is often limited by their static position, which only allows optimal energy capture at certain angles throughout the day. To overcome this challenge, a solar tracker system was developed that automatically adjusts the panel’s position to follow the sun’s movement, enhancing energy capture efficiency. This study explores the implementation of a solar tracker using a Real Time Clock (RTC) and the Naive Bayes method to optimize panel orientation based on the sun’s position. The system, controlled by the NodeMCU ESP32 and powered by an MG995 servo motor, predicts sun movement using historical data for proactive adjustments. Testing shows a 5.47% improvement in energy efficiency over conventional systems, demonstrating its potential in renewable energy applications.